Cultivating reasonableness in education community of philosophical inquiry - Mancenido-Bolaños, Marella Ada V.; Alvarez-Abarejo, Cathlyne Joy P.; Marquez, Leander Penaso (Integrated science series, 2023)
This book focuses on the real-world application of the Philosophy for/with Children (P4wC) pedagogy to cultivate reasonableness in individuals through communities of philosophical inquiry. It presents a collection not only of theories but, more importantly, of experiences, discoveries, and innovations on P4wC by scholars, trainers, advocates, and practitioners around the world. Each chapter provides readers with insights and lessons that have resulted from the continuous application, exploration, and enrichment of the concepts, principles, and practices that were developed by Matthew Lipman and Ann Margaret Sharp into what P4wC is today - a dialogic pedagogical approach that may just be what is needed at a time when reasonableness and dialogue are essential to maintaining global stability and progress. In this light, this book also looks into how the P4wC approach can be practiced with adults such as when it is employed in various settings or contexts such as in business consulting, textbook writing, peace education, and extremism prevention, among others. Furthermore, this book also features chapters that discuss how the P4wC pedagogy can be beneficial once integrated into processes such as classroom teaching, teacher education, bioethics, and employee education. This book provides valuable insights about how reasonableness that is cultivated through building communities of philosophical inquiry in education can be a powerful tool for nation-building and social transformation